(untitled) (Third Sector Social Economic Review, 2024)
Abstract Counterproductive work behavior (CWB) is defined as the intentional and voluntary behavior of organizational employees that causes material and moral harm to the organization. These behaviors disrupt the general climate of the organization, negatively affect its productivity, and prevent financial losses as well as the achievement of organizational goals. In today’s conditions where competition is intense, counterproductive work behaviors are among the issues that managers especially focus on. According to the results of the research conducted on this subject, these behaviors are considered as retaliatory behaviors developed by employees against the management who cannot find what they expect from the organization in accordance with the psychological contract within the organization. These behaviors, known as the dark side of employee behavior, have a wide scope of application. Verbal and physical attack, non-compliance with organizational rules, absenteeism, slowing down work, theft, sabotage, misusing the organization’s resources and time, etc. consists of behaviors. Counterproductive work behavior, which is legally considered as the employee’s failure to fulfill his duty of care and loyalty, has significant legal consequences for the employee if detected. In this study, the current situation of employees whose employment contracts were terminated due to counterproductive work behavior was examined within the scope of the Supreme Court decisions. The case study method was used in the study, and the Supreme Court decisions associated with counterproductive work behaviors between 2018 and 2023 were evaluated. As a result of the events examined, sabotage and production deviation behaviors were valid grounds for termination; Behaviors such as withdrawal, theft and abuse have been determined as justified grounds for termination.